Evaluation and Strategy for Improving HR Performance at PT Mestika Nusantara Agrokimia - Ramadhan, Novta Fardhika; Kusumaningtyas, Menur (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate and improve the performance of human resources (HR) at PT Mestika Nusantara Agrokimia, a manufacturer of herbicide chemicals. The method used was descriptive qualitative through direct observation and distributing questionnaires to five key employees. The results show that low HR performance is caused by unclear division of tasks, unstructured workload, limited work facilities, lack of rewards, and lack of feedback. Work safety conditions are also a concern due to the lack of personal protective equipment (PPE). This study recommends improving work facilities, explaining job descriptions, proper reward systems, and periodic performance evaluations to increase productivity and job satisfaction.